Targeted next-generation sequencing identifies a novel frameshift EYA1 variant causing branchio-otic syndrome in a Chinese family. (November 2020) - Xing, Zhan-Kui; Wang, Su-Yang; Xia, Xin; Ding, Wen-Juan; Duan, Lei; Cui, Xiao; Xu, Bai-Cheng; Zhu, Yi-Ming; Liu, Xiao-Wen
Abstract: Objective: To evaluate the genotype-phenotype correlation of branchio-otic syndrome (BOS) in a Chinese family. Methods: The proband in this study was an 18-month-old boy with hearing loss, preauricular pit, and branchial fistula without a renal anomaly. We collected blood samples from 6 family members, including 4 who were affected by the syndrome. Targeted next-generation sequencing and Sanger sequencing were performed to identify pathogenic mutations in this family. Results: Pedigree analysis indicated that the mode of inheritance in the family was consistent with the autosomal dominant pattern. Hearing loss was the most common manifestation, occurring in 4 patients. Other findings included preauricular pits (n=2), cervical fistulas (n=3) and abnormal pinnae (n=4). None of the patients had renal anomalies. Evaluation by pure-tone audiometry and temporal bone imaging demonstrated bilateral mixed hearing loss, as well as middle ear and inner ear deformities, in two patients. Mutational analysis of candidate genes in the selected patients led to the identification of a novel frameshift variant NM_000503.4: c.1075_1077delinsAT (p.Gly359Ilefs*7) in the EYA1 gene. Conclusions: The EYA1 c.1075_1077delinsAT mutation is the causative variant in the Chinese family with BOS, although the penetrance is variable within patients.